Influence of Urbanization on Social Connections in Informal Settlements of Bharatpur Metropolitan City, Nepal - Sapkota, Keshab Raj (Madhyabindu Journal, 2026)
Urbanization is rapidly reshaping social structures in developing countries, particularly in informal settlements where housing, infrastructure, and access to basic services are often inadequate. This study examines the impact of urbanization on social networks in informal settlements of Bharatpur Metropolitan City, Nepal, a fast-growing urban center with diverse residential conditions. Guided by Social Network Theory and Social Capital Theory, the research investigates whether urban growth, housing type, and access to services influence the quality, frequency, and strength of social interactions and support systems. Data were collected from 200 households using stratified random sampling, with one adult respondent from each household interviewed through structured face-to-face surveys. The data were analyzed using descriptive statistics, bivariate analysis, logistic regression, and factor analysis. The findings reveal that urbanization, housing type, and access to basic services do not have a statistically significant effect on social ties. Despite poor infrastructure and economic challenges, strong social relationships persist due to cultural values, community cooperation, and informal support systems. The study highlights the importance of strengthening community networks alongside physical infrastructure to promote inclusive, resilient, and socially cohesive urban development.